Czech idioms with the component 'body' and their translation into Macedonian (Slavic Studies, 2024)
The subject of interest in this paper is the idioms with a key somatic component ‘body’ in the Czech works translated into Macedonian. Each scheme is analysed from the aspect of specifics and characteristics which can be found in the idioms, as well as from the aspect of the reality which they interpret and value.
Keywords: Czech idioms; Macedonian idioms; body; translation